"Cute saves the world!": animal Internet Celebrities' cute activism in the #adoptdon'tshop animal rescue campaign on social media. - Lee, Jin (Social Movement Studies, 2026)
This paper examines everyday media practices and seamless work in animal advocacy by various actors with different levels of internet celebrity status, who curate their media personas around 'cute' animal images, including established pet Influencers and animal internet celebrities. Through a case study of the most prominent (hashtag) campaign and movement against the pet trade industry and culture in South Korea, #AdoptDon'tShop [#사지말고입양하세요, sajimalgo-ipyanghaseyo], I explore animal internet celebrities' media practices and immaterial labor that are understated but rigorously performed out of compassion and care for animals. Taking up scholarship on cuteness and Influencer culture, I introduce the concept of cute activism, a novel iteration of social movements adapted into visual social media cultures, pivoting on the performative potential of cuteness and its inherent competency in navigating increasingly-visualized, attention-seeking social media environments. While the instinctive affective appeal of cuteness serves as a driving force and primary modality of cute activism, effectively attracting more people to be tuned into messages, events, and ultimately movements, the very appeal may come into being as a burden for activists, inducing them into continuous immaterial labor.